Micro/nanoscale biochar facilitates cadmium immobilization and soybean resilience: Insights from microbial life-history strategies and plant physiological response - Yaping Wang; Yichen Xu; Yini Cao; Yi Hu; Changrui Liu; Chuanxin Ma; Wende Yan (Bioresource Technology, 2026)

Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

High-accuracy EEG-based driver fatigue detection using feature-coupled tensor decomposition for multimodal brain connectivity analysis - Tian Yan; Hechong Su; Zengyao Yang; Aimin Zhang; Yidan Ma; Xiaolong Wang; Yue Wu; Li Yan; Yichen Wang; Jianfu Cao (Cognitive Neurodynamics, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Heterogeneous rock abundances in the lunar subsurface revealed by cold-spot craters - Yizhen Ma; Zhiyong Xiao; Yichen Wang; Yiren Chang; Rui Xu; Yan Su (Icarus, 2026)

Sublethal effects of field-recommended glyphosate exposure on the predatory insect Arma chinensis: Growth inhibition and reproductive costs - Zhihan Su; Wenyan Xu; Luyao Fu; Dianyu Liu; Xiaoyu Yan; Yu Chen; Yichen Wang; Chenxi Liu (Environmental Pollution, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Silicon nanoparticles promote soybean growth in Cd-contaminated soil by modulating soil bacterial networks - Zihan Luo; Jiajia Ma; Yini Cao; Yichen Xu; Chuanxin Ma; Jun Wang; Wende Yan (Applied Soil Ecology, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

Intercropping enhances soil aggregate stability and associated organic carbon via divergent microbial assembly and co-occurrence networks - Yazhen Chen; Wenqiong Jiang; Yuanying Peng; Yichen Xu; Haobo Xu; Juan Chen; Xiaozhou Huang; Jinsong He; Xiaohong Wu; Jun Wang; Jianbo Jia; Wende Yan (Agriculture, Ecosystems & Environment, 2026)

Vinpocetine attenuates myocardial ischemia/reperfusion injury in mice by suppressing oxidative stress, inflammation, and apoptosis - Tianchen Xia; Yichen Qian; Yilong Jiang; Qiang Zhang; Jiahao Pan; Hui Xiong; Jiaxin Zhang; Taotao Yan; Qi Li; Shenjie Zhang; Qingsheng You (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Amino Acid Metabolic Remodeling in Bivalves Under Environmental Stress: Roles, Mechanisms, and Implications for Bivalve Health—A Review - Yichen Lin; Wei Chen; Jixing Peng; Xinnan Zhao; Yan Di; Mengmeng Guo; Yanfang Zhao; Haiyan Wu; Guanchao Zheng; Qianqian Geng; Zhijun Tan (Fishes, 2026)
Climate change and increasing instability in coastal marine environments have intensified stressors such as elevated temperature, hypoxia, salinity variation, and pollutant exposure, posing major challenges to the survival, health, and culture performance of bivalves. As economically important aquaculture species and key components of coastal ecosystems, bivalves are highly sensitive to environmental fluctuations, making their metabolic responses highly relevant to both physiological adaptation and aquaculture sustainability. Increasing evidence indicates that metabolic remodeling is an important adaptive strategy supporting bivalve tolerance to environmental stress, with amino acid metabolic remodeling emerging as one of its most sensitive and functionally important components. This review summarizes the major response patterns, key pathways, and potential regulatory mechanisms of amino acid metabolism in bivalves under different stress conditions. Different environmental stressors induce distinct yet integrated shifts in amino acid metabolism, including enhanced catabolism, carbon–nitrogen redistribution, osmotic regulation, and antioxidant defense, thereby supporting energy homeostasis and physiological stress tolerance in bivalves. By highlighting amino acid metabolic remodeling as a central mechanism of bivalve adaptation to environmental stress, this review provides insights into adaptive responses, metabolite-based indicators for monitoring aquaculture environments and bivalve health, and management strategies for improving resilience in bivalve aquaculture.

Collaborative optimization pathway of provincial power generation structure in China - Yan Nie; Guoxing Zhang; Yutao Wang; Bin Su; Yichen Feng; Lean Yu (Mitigation and Adaptation Strategies for Global Change, 2026)

3D Patellar Shape is Associated with Patellar Dislocation: an Automated Coordinate Algorithm and Statistical Shape Modeling Analysis - Yichen Yan; Jie Yao; Zifan Liu; Qinqin Yang; Bin Sun; Xinguang Liu; Bin Yang; Yubo Fan (Annals of Biomedical Engineering, 2026)

Recent Advances and Future Perspectives in the Integrated Management of Potato Bacterial Wilt - Shifeng Liu; Yichen Wang; Juqin Wang; Lang Yan; Xianjun Lai; Deshui Yu (Potato Research, 2026)

Isolation, characterization and biotechnological potential of a contaminant-derived cyanobacterium Sodalinema sp. ZYS - Yang Zhao; Zhichao Zhang; Yue Qiao; Yichen Li; Xiang Liu; Yan Liu; Tao Zhu; Xuefeng Lu (Bioresource Technology, 2026)

Plant patches maintain soil nematode abundance and energy flow but not community structure in severely-degraded alpine grasslands in the Qinghai-Tibetan Plateau - Jie Wen; Tao Liu; Xiaoli Wang; Junjie Lei; Chunhui Zhang; Zhilei Li; Yichen Xu; Yuan Ma; Buqing Zhong; Xiaocui Liang; Wende Yan; Yushou Ma; et al. (Journal of Environmental Management, 2026)

Catalytic pyrolysis of wood-plastic composites using nickel-modified red mud for enhanced hydrogen and aromatic production - Yichen Yan; Huichao Suo; Cheng Peng; Zhengyi Wu; Lan-Lan Lou; Shuangxi Liu; Kai Yu (Bioresource Technology, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Century-long socioeconomic-air pollution transitions revealed by lake sediments in Northeast China - Yalan Tang; Yongming Han; Yichen Wang; Dongna Yan; Shaolong Sun; Qiyuan Wang; Dewen Lei; Hao Peng; Peng Yao; Zeyu Liu; Ulrike Dusek (Global and Planetary Change, 2026)

Nonlinear Dynamics and Control of Tension Leg Platform Floating Wind Turbines: A Review - Jiawen Li; Lei Yan; Guibin Chen; Yichen Jiang; Mingfu Tang (Journal of Marine Science and Engineering, 2026)
As offshore wind power development advances into deeper waters, tension leg platform (TLP) floating wind turbines stand out for their excellent motion performance, lightweight structure design, and minimal seabed footprint. This paper reviews the advancements in TLP technology, covering structural configurations, dynamic characteristics and control strategies. Particular emphasis is given to analyzing dynamic response under combined environmental loads, including nonlinear motions induced by higher-order wave forces and parametric excitations, as well as the multiphysics coupling mechanisms involving aerodynamics, hydrodynamics, servo control, and structural dynamics. The review concludes by outlining future trends in platform scaling, intelligent operation and maintenance, and multi-energy integration. Overall, this review provides strategic insights for further research and engineering applications of TLP floating wind turbines.

Ribavirin acts as a candidate insect growth regulator: Providing sustainable control potential for Rhopalosiphum padi - Li Xu; Jingkun Li; Fei Miao; Zhiwen Zhao; Yichen Fu; Hengxu Yan; Sen Huang; Hao Yu; Runqiang Liu; Dongzhi Li (Crop Protection, 2026)

Performance Comparison of CPD, NRICP, and Spherical Parameterization on Femoral Statistical Shape Model - Qinqin Yang; Yichen Yan; Bin Yang; Liang Yuan; Jie Yao; Fang Pu (Journal of Medical and Biological Engineering, 2026)

Targeted breeding of Litopenaeus vannamei for resistance to acute hepatopancreatic necrosis disease using the IRF-SSR molecular marker - Bin Yin; Yang Hu; Xuheng Yan; Yibin Chen; Yichen Hu; Sedong Li; Chaozheng Li; Jianguo He (Aquaculture, 2026)

Nonlinear responses of dryland vegetation GPP to climate and human drivers along aridity gradients in China and Mongolia - Haitao Zhang; Yifan Lu; Peng Tian; Yichen Yan; Ruoyu Wang; Shengnan Zhang; Weifeng Wang; Eerdun Hasi; Yingjun Xu (Journal of Environmental Management, 2025)

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Salix×jiangsuensis ‘J172’ enhanced lead tolerance under flooding stress by regulating the rhizosphere bacterial assembly and functions - Yichen Xu; Yazhen Chen; Yini Cao; Jason C. White; Hao Yu; Chuanxin Ma; Wende Yan; Baoshan Xing (Environmental Pollution, 2025)

Spatiotemporal warning of rainfall-induced railway geohazards in China - Bohao Li; Kai Liu; Ming Wang; Weihua Zhu; Ziyu Jiang; Ningning Qiao; Yichen Yan; Junfei Liu; Jing Zhao; Chenxia Li (Engineering Geology, 2025)

Quinoa greens as a novel plant food: a review of its nutritional composition, functional activities, and food applications - Huange Huang; Qiang Wang; Jianxin Tan; Chunxiang Zeng; Junying Wang; Jingwei Huang; Yichen Hu; Qi Wu; Xiaoyong Wu; Changying Liu; Xueling Ye; Yu Fan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Incorporation of disulfide bonds into ionizable lipids enables efficient splenic mRNA delivery and potent immunotherapy in mice - Yichen Li; Yi Cao; Hao Bai; Luwei Zhang; Baiqiu Chen; Chengfan Wu; Qi Shuai; Yunfeng Yan (Chemical Engineering Journal, 2025)

Short-Term Postoperative Mechanical Properties of Graft in Anterior Cruciate Ligament Reconstruction - Zizhan Lian; Bin Sun; Xiangfei Kong; Yichen Yan; Jie Yao; Bin Yang; Yubo Fan (Journal of Medical and Biological Engineering, 2025)

Ceramic ultrafiltration membrane as pretreatment for drinking water nanofiltration treatment: Performance, cleaning, and costs based on an engineering case - Yawei Xie; Chengyue Fan; Yichen Fang; Xiwang Zhu; Jiaming Yan; Haodong Liu; Hongyuan Liu (Journal of Cleaner Production, 2025)

Impact of fallen wood on soil protists in the subtropics - Yichen Xu; Yini Cao; Yazhen Chen; Zhe He; Wende Yan; Jun Wang (Plant and Soil, 2025)

Ethylene glycol conversion to glycolic acid in Escherichia coli: Leveraging transcriptomic data for enhanced productivity - Yichen Gong; Wenlong Yan; Fei Liu; Mingzhu Ding; Yingjin Yuan (Journal of Environmental Chemical Engineering, 2025)

Janus antistatic protective clothing for personal sweat management and electrostatic protection - Haojun Luo; Yichen Tang; Xianchang Wu; Yu Zhang; Shuqiang Min; Yijie Zhu; He Wang; Tonghuan Zhan; Zixuan Xu; Zhihao Chen; Xiaohua Yu; Heng Wang; et al. (Chemical Engineering Journal, 2025)

Tanshinone IIA mitigates postoperative cognitive dysfunction in aged rats by inhibiting hippocampal inflammation and ferroptosis: Role of Nrf2/SLC7A11/GPX4 axis activation - Yan Yang; Bo Wang; Yichen Jiang; Wan Fu (NeuroToxicology, 2025)

Exploring tourists' perceptions of ecosystem services in national parks to guide the optimization of management - Xiaomin Xiao; Yichen Yan; Yuxin Qi; Qiaoru Ye; Qiwen Yu; Keren He; Ruiming Xiao; Xue-Chao Wang; Xiaobin Dong (Journal of Cleaner Production, 2025)

Greener is not always better: Exploring the non-linear relationships between three-dimensional green and gray spaces exposure and various physical activities - Yuheng Mao; Tianyu Xia; Fan Hu; Jinyu Hu; Yichen He; Jingheng Yan; Ling Wang; Hongmei Xu; Jinguang Zhang; Dan Chen (Building and Environment, 2025)

Human body convective heat transfer coefficient under non-stationary turbulent wind - Siqi Zhou; Yichen Yu; Jianlei Niu; Kenny C.S. Kwok; Kapil Chauhan; Kam Tim Tse; Xinzi Xu; Sam Ho Yan Wong (Building and Environment, 2025)

Response of bacterial and fungal composition in tailings to Mn pollution - Junjie Lei; Qing Dan; Wende Yan; Ting Liu; Yakov Kuzyakov; Wei Wang; Yichen Xu; Junwu Liu; Yingchun Fang; Jun Wang; Xiaohong Wu (Journal of Hazardous Materials, 2024)

Midseason drying increases soil dissolved organic carbon and rice yield via soil cbbL bacteria - Jinsong He; Wei Wang; Ting Liu; Wende Yan; Xiaohong Wu; Junjie Lei; Yichen Xu; Yazhen Chen; Yuxin Yao; Wenqiong Jiang; Zhentao Shen; Asma Farooq (Journal of Environmental Management, 2024)

Characterization and immune role of class B scavenger receptor member 1 in spotted sea bass (Lateolabrax maculatus) - Yichen Fu; Chao Zhao; Changhong Lin; Bo Zhang; Lulu Yan; Bo Zhang; Pengfei Wang; Lihua Qiu (Fish & Shellfish Immunology, 2024)

Nitrogen availability and its related enzyme activities affect microbial residue nitrogen accumulation during Chinese fir plantation development - Junjie Lei; Peng Dang; Xiaoqian Gao; Yichen Xu; Ting He; Zongxin Liu; Wende Yan (Applied Soil Ecology, 2024)

Lightweight, high-strength and fireproof borax-crosslinked graphene/hydroxyethyl cellulose hybrid aerogels fabricated via ice template method - Junjiao Li; Chao Sui; Chenxi Zhao; Gong Cheng; Zifu Zang; Lei Wen; Yuna Sang; Yichen Zhou; Yushun Zhao; Xin Yan; Xiaodong He; Chao Wang (Chemical Engineering Journal, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

The greener the living environment, the better the health? Examining the effects of multiple green exposure metrics on physical activity and health among young students - Yuheng Mao; Tianyu Xia; Fan Hu; Dan Chen; Yichen He; Xing Bi; Yangcen Zhang; Lu Cao; Jingheng Yan; Jinyu Hu; Yanzi Ren; Hongmei Xu; et al. (Environmental Research, 2024)

Biological performance and membrane fouling of a microalgal-bacterial membrane photobioreactor for wastewater treatment without external aeration and carbonation - Zhaozhao Wang; Yichen Liao; Lina Yan; Baoqiang Liao (Environmental Research, 2024)

Exploring metal(loid)s dynamics and bacterial community shifts in contaminated paddy soil: Impact of MgO-laden biochar under different water conditions - Yan Wang; Yichen Wang; Suhan Ma; Kankan Zhao; Fenghua Ding; Xingmei Liu (Environmental Pollution, 2024)

The social network perspective on power system co-evolution: responses to “double carbon target” realization in China - Xiulin Gao; Guoxing Zhang; Yan Nie; Xi Xi; Yichen Feng (Environmental Science and Pollution Research, 2024)

Development of a dual-functional inhibitor for natural gas hydrates and construction of drilling fluid system - Jintang Wang; Zhijun He; Yichen Yan; Lei Liu; Jin Yan; Bo Liao; Ke Zhao; Yiyao Li; Longqiao Chen (Gas Science and Engineering, 2024)

Influence of Natural Gas Hydrate Distribution Patterns on the Macroscale–Mesoscale Mechanical Properties of Hydrate-Bearing Sediments - Yujing Jiang; Xiaoyu Du; Peng Yan; Meng Li; Hengjie Luan; Xianzhuang Ma; Yichen Shi (Journal of Marine Science and Engineering, 2023)
Studying the mechanical characteristics of hydrate-bearing sediments (HBS) contributes to the comprehensive understanding of the mechanical behavior in environments with natural gas hydrate (NGH) occurrences. Simultaneously, the distribution patterns of hydrates significantly influence the strength, deformation, and stability of HBS. Therefore, this paper employs particle flow code (PFC) to conduct biaxial discrete element simulations on specimens of HBS with different hydrate distribution patterns, revealing the macroscale–mesoscale mechanical properties, evolution patterns, and destructive mechanisms. The results indicate that the strain-softening behavior of HBS specimens strengthens with the increase in hydrate layer thickness, leading to higher peak strength and E50 values. During the gradual movement of the hydrate layer position (Ay) from both ends to the center of the specimen (Ay = 0.40 mm → Ay = 20 mm), the strain-softening behavior weakens. However, when Ay = 20 mm, the specimen exhibits evident strain-softening behavior again. Moreover, with an increase in the angle between the hydrate layer and the horizontal direction (α) greater than 20°, the peak strength of the specimen increases, while E50 shows an overall decreasing trend. The influence of axial loads on the hydrate layer in specimens varies with α, with larger contact forces and fewer cracks observed for higher α values.

The Responses of Continuous Knee Passive Stiffness Following Fatigue - Xiangfei Kong; Zizhan Lian; Yichen Yan; Jie Yao; Yubo Fan (Journal of Medical and Biological Engineering, 2023)

Fluid tunnel research for challenges of urban climate - Yongling Zhao; Lup Wai Chew; Yifan Fan; Christof Gromke; Jian Hang; Yichen Yu; Alessio Ricci; Yan Zhang; Yunpeng Xue; Sofia Fellini; Parham A. Mirzaei; Naiping Gao; et al. (Urban Climate, 2023)

AGHRNet: An attention ghost-HRNet for confirmation of catch‐and‐shake locations in jujube fruits vibration harvesting - Zhouzhou Zheng; Yaohua Hu; Taifeng Guo; Yichen Qiao; Yong He; Yan Zhang; Yuxiang Huang (Computers and Electronics in Agriculture, 2023)

Dynamic response analysis of a floating vertical axis wind turbine with helical blades based on the model test - Wanru Deng; Ying Guo; Liqin Liu; Yan Li; Yichen Jiang; Peng Xie (Ocean Engineering, 2023)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Decay of fallen wood and elevation affects soil fungal community assembly and indirectly controls community diversity - Yichen Xu; Yazhen Chen; Peng Dang; Xingjian Jiang; Wei Zheng; Junjie Lei; Wende Yan (Applied Soil Ecology, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Continuous flow modulates zein nanoprecipitation solvent environment to obtain colloidal particles with high curcumin loading - Haocheng Guo; Yiming Feng; Yong Deng; Tianyi Yan; Zimo Liang; Yichen Zhou; Wei Zhang; Enbo Xu; Donghong Liu; Wenjun Wang (Food Hydrocolloids, 2023)

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

Discrete Element Simulation of the Macro-Meso Mechanical Behaviors of Gas-Hydrate-Bearing Sediments under Dynamic Loading - Yujing Jiang; Meng Li; Hengjie Luan; Yichen Shi; Sunhao Zhang; Peng Yan; Baocheng Li (Journal of Marine Science and Engineering, 2022)
Under the action of dynamic loadings such as earthquakes and volcanic activities, the mechanical properties of gas-hydrate-bearing sediments will deteriorate, leading to a decrease in the stability of hydrate reservoirs and even inducing geological disasters such as submarine landslides. In order to study the effect of dynamic loading on the mechanical properties of hydrate sediments, triaxial compression tests of numerical specimens were carried out by using particle flow code (PFC2D), and the macro-meso mechanical behaviors of specimens were investigated. The results show that the loading frequency has a small effect on the stiffness of the hydrate sediment, while it has a large effect on the peak strength. The peak strength increases and then decreases with the increase in loading frequency. Under the same loading frequency, the peak strength of the hydrate sediment increases with the increase in loading amplitude, and the stiffness of the specimen decreases with the increase in loading amplitude. The maximum shear expansion of the specimen changes with the movement of the phase change point and the rearrangement of the particles. The maximum shear expansion of the specimen changes with the movement of the phase change point and the change of the bearing capacity of the particles after the rearrangement, and the more forward the phase change point is, the stronger the bearing capacity of the specimen in the plastic stage. The shear dilatancy angle and the shear dilatancy amount both increase linearly with the increase in loading amplitude. The influence of loading frequency and amplitude on the contact force chain, displacement, crack expansion, and the number of cementation damage inside the sediment is mainly related to the average axial stress to which the specimen is subjected, and the number of cracks and cementation damage of the sediment specimen increases with the increase in the average axial stress to which the sediment specimen is subjected. As the rate of cementation damage increases, the distribution of shear zones becomes more obvious.

Spatial-temporal distributions and influential factors of phthalate acid esters in sediments of three lakes in Inner Mongolia - Yan Ma; Tong Liu; Bo-Tao Zhang; Yan Liu; Peng Shao; Chen Sun; Yichen Zhang; Jiale Bi; Yunkai Dong; Shengrui Wang; Guoming Zhang (Environmental Science and Pollution Research, 2022)

Degradation of the ciprofloxacin antibiotic by photo-Fenton reaction using a Nafion/iron membrane: role of hydroxyl radicals - Fei Wang; Yichen Zhang; Hao Ming; Li Wang; Zhongyuan Zhao; Yuehong Wang; Jiyan Liang; Yan Qin (Environmental Chemistry Letters, 2020)